Clinical Management and Histopathological Findings of Vaginal Myxoma and Fibroma in Female Dogs - Verma, Atul Kumar; Gupta, Ratan; Verma, Pradeep Kumar; Kumar, Shubham; Singh, Nagendra; Jaiswal, Vikas; John, Jeny K; Tripathi, Ashutosh; Singh, Ajit Kumar; Shukla, Manish Kumar (The Indian Journal of Animal Reproduction, 2023)
Five female dogs were presented at Veterinary Clinical Complex, College of Veterinary and Animal Sciences, Sardar Vallabh Bhai Patel University of Agriculture & Technology, Meerut, Uttar Pradesh with the history of protruded mass from the vagina, suspected for myxomas and fibroma. The animals were anorexic, dull with slightly elevated temperature. Confirmatory diagnosis were made by histopathological examination of these tissues. Two of the she dogs were diagnosed with Vaginal Myxoma and other three were diagnosed with Fibroma. The treatment included surgical removal of protruded mass with follow-up treatment with antibiotics, NSAIDS and multi-mineral and multi-vitamin supplements.
Keywords: Myxoma; Fibroma; Vaginal tumour; Female dog